RESEÑA de: Radicalism and Terrorism in the 21 st Century. Implications for Security. Studies in politics, security and society Vol.9. Peter Lang Edition. Frankfurt, 2017. 321 págs. Anna Sroka, Fanny Castro-Rial Gorrone, Rubén Darío Torres Cumbrián (eds.) - López Serrano, Aída (Revista de Derecho de la UNED (RDUNED), 2017)
-